Idobata-Nagaya: a community housing solution for socially isolated older adults following the great East Japan earthquake - Toshiki Abe; Hiroaki Saito; Hiroaki Saito; Nobuaki Moriyama; Naomi Ito; Morihito Takita; Yuri Kinoshita; Yuri Kinoshita; Akihiko Ozaki; Yoshitaka Nishikawa; Yoshitaka Nishikawa; Chika Yamamoto; et al. (Frontiers Media S.A., 2023)
IntroductionFollowing the Great East Japan Earthquake, the living environment of socially isolated older adults has become a pressing concern. In response, Nagaya, a collective housing program, was established in Soma City, Fukushima, Japan to address social isolation among older adults and support their long-term health. This study aimed to identify characteristics of individuals in Nagaya and examine the sustainability of this initiative.MethodsWe conducted a retrospective analysis of residents who were relocated to Nagaya, emphasizing their characteristics, the continuity of their stay in Nagaya, and their care certification levels, using data up to December 31, 2022. We employed Kaplan-Meier curves to analyze the duration for which residents continued to reside in Nagaya and the time leading up to the requiring care-level certification.ResultsOf 65 people who moved to Nagaya after the disaster, 30 people (46.2%) continued to live there, 21 (32.3%) died during their stay, and 14 (21.5%) moved out. The overall duration of occupancy averaged 6.39 years (SD 3.83 years). The proportion of requiring care-level certification occurrences per person-year was 0.0577 for those without care certification and 0.3358 for those with requiring support level at the time of moving in.ConclusionIn summary, Nagaya-style communal housing may offer suitable living environments for older adults with diverse needs during disasters and serve as a valuable tool for developing public policies in aging societies.